Calculus with Applications (10th Edition)

Published by Pearson
ISBN 10: 0321749006
ISBN 13: 978-0-32174-900-0

Chapter R - Algebra Reference - R.3 Rational Expressions - R.3 Exercises: 38

Answer

$\dfrac{5x+2}{x^{2}-1}+\dfrac{3}{x^{2}+x}-\dfrac{1}{x^{2}-x}=\dfrac{5x^{2}+4x-4}{x(x+1)(x-1)}$

Work Step by Step

$\dfrac{5x+2}{x^{2}-1}+\dfrac{3}{x^{2}+x}-\dfrac{1}{x^{2}-x}$ Factor the denominators of all three fractions: $\dfrac{5x+2}{x^{2}-1}+\dfrac{3}{x^{2}+x}-\dfrac{1}{x^{2}-x}=...$ $...=\dfrac{5x+2}{(x-1)(x+1)}+\dfrac{3}{x(x+1)}-\dfrac{1}{x(x-1)}=...$ Evaluate the indicated operations using the LCD, which is $x(x-1)(x+1)$ in this case: $...=\dfrac{(5x+2)(x)+3(x-1)-(x+1)}{x(x+1)(x-1)}=...$ Simplify: $...=\dfrac{5x^{2}+2x+3x-3-x-1}{x(x+1)(x-1)}=...$ $...=\dfrac{5x^{2}+4x-4}{x(x+1)(x-1)}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.